(untitled) (LEARNing Landscapes, 2013)
This paper presents an experience of integrating digital technology with traditional historical research in a grade 11 history classroom. Students researched First World War soldiers from western Quebec using online databases and archival sources and presented their research using a Wordpress blog and Google Earth. Students built their sense of historical consciousness by connecting to the past of their community and developing disciplinary skills such as using primary sources. Throughout the project, students were engaged in the authentic task. The success of the project indicates that teachers should be encouraged to use more digital technology in the history classroom.